2020
DOI: 10.3390/molecules25020279
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Psoralea corylifolia L. Based on High-Speed Countercurrent Chromatographic Fingerprinting

Abstract: Traditional Chinese medicine (TCM)has played an important role in promoting the health of Chinese people. The TCM Psoralea corylifolia L. has been used in the treatment of various kinds of diseases including enuresis, vitiligo, and calvities. However, therapeutic effects of P. corylifolia L. have often influenced by the quality of plants. So, it is very important to control the quality of P. corylifolia L. In this study, analytical high-speed countercurrent chromatography (HSCCC) was successfully used to finge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A study used HSCCC fingerprint to control the quality of PCL, it was found that the chemical components of 20 batches of Chinese herbal medicines were similar, but their contents were quite different. At the same time, it was confirmed that the HSCCC approach had good reproducibility, precision, and stability, providing a solid foundation for the quality control of PCL and having the potential to be utilized to identify plant medicinal materials [ 177 ]. By combining the HPLC fingerprint and multi-component analysis, the quality of PCL was assessed.…”
Section: Quality Controlmentioning
confidence: 99%
“…A study used HSCCC fingerprint to control the quality of PCL, it was found that the chemical components of 20 batches of Chinese herbal medicines were similar, but their contents were quite different. At the same time, it was confirmed that the HSCCC approach had good reproducibility, precision, and stability, providing a solid foundation for the quality control of PCL and having the potential to be utilized to identify plant medicinal materials [ 177 ]. By combining the HPLC fingerprint and multi-component analysis, the quality of PCL was assessed.…”
Section: Quality Controlmentioning
confidence: 99%
“…Generally, the K D value for the target component is usually expected to be between 0.5 and 2.0. If the K D value is under 0.5, the solute will be eluted near the solvent front, which may result in peak resolution loss and poor separation performance; if the K D value is much greater than 2.0, the solute will elute in an excessively broad peak and may lead to a longer elution time, reduced column efficiency, and wasted solvent [ 36 , 37 , 38 ]. Meanwhile, the stationary phase retention can reflect the exaction rate during HSCCC separation.…”
Section: Resultsmentioning
confidence: 99%
“…3c). [3][4][5] Other components in PCL mainly include trace elements such as potassium, manganese, calcium and selenium, lipids such as monoglyceride, diglyceride, triglyceride and free fatty acid, glycosides such as daucosterol, methylglycoside and PCL polysaccharide, as well as fatty acids in volatile oils and non-volatile terpenoid oils such as palmitic acid, oleic acid, linoleic acid and stearic acid.…”
Section: Main Chemical Components Of Pclmentioning
confidence: 99%